Detailed Structure–Function Correlations of Bacillus subtilis Acetolactate Synthase. Issue 1 (13th November 2014) - Sommer, Bettina; von Moeller, Holger; Haack, Martina; Qoura, Farah; Langner, Clemens; Bourenkov, Gleb; Garbe, Daniel; Loll, Bernhard; Brück, Thomas
Abstract Isobutanol is deemed to be a next‐generation biofuel and a renewable platform chemical.1 Non‐natural biosynthetic pathways for isobutanol production have been implemented in cell‐based and in vitro systems with Bacillus subtilis acetolactate synthase (AlsS) as key biocatalyst.2–6 AlsS catalyzes the condensation of two pyruvate molecules to acetolactate with thiamine diphosphate and Mg2+ as cofactors. AlsS also catalyzes the conversion of 2‐ketoisovalerate into isobutyraldehyde, the immediate precursor of isobutanol. Our phylogenetic analysis suggests that the ALS enzyme family forms a distinct subgroup of ThDP‐dependent enzymes. To unravel catalytically relevant structure‐function relationships, we solved the AlsS crystal structure at 2.3 Å in the presence of ThDP, Mg2+ and in a transition state with a 2‐lactyl moiety bound to ThDP. We supplemented our structural data by point mutations in the active site to identify catalytically important residues.